Empowering Farmers to Encourage Social Change During the COVID-19 Pandemic in Banten Province - Tauchid S., Agus M.; Bekti, Herijanto; Pancasilawan, Ramadhan; Karlina, Nina (KnE Social Sciences, 2022)
This research examined the efforts carried out by the Banten Provincial Government in empowering farmers to encourage social change during the COVID- 19 pandemic. Qualitative methods were used with an exploratory approach. Data were collected by interview and documentation methods. The results showed that the Banten Provincial Government tried to empower farmers by: providing support for food production in the form of seeds, fertilizers, and agricultural machinery; assisting agricultural production through “field school” activities that included providing education and direct field practice to farmer groups; and enabling farmers to actively participate in agricultural production activities through conducting continuous monitoring and evaluation of various assistance and activity programs that have been provided to farmers in need. These efforts to empower farmers led to an increase in food production in Banten Province, especially for rice commodities. Another impact was increased social changes experienced by farmers through the use of appropriate technology and agricultural mechanization, which encouraged agricultural production to become more efficient, thereby increasing the Banten Province farmer’s exchange rate. Farmer empowerment will have a major impact on food availability, especially during the pandemic, and therefore social changes for farmers in the use of agricultural technology are important. Keywords: empowerment, farmer, social change